KEBIJAKAN KRIMINAL DALAM UPAYA PENANGGULANGAN TINDAK PIDANA PENCURIAN HEWAN DI KABUPATEN PADANG LAWAS UTARA - Muhammad Azhali Siregar; Syafruddin Kalo; Madiasa Ablisar; Rosnidar Sembiring (Universitas Sumatera Utara, 2017)
ABSTRACT Criminal wisdom or criminal polities was an effort which rational from society to cope crime. Efforts or wisdom to cope from superintended of crime in particular livestock coutent of aspect criminal wisdom. Remembered efforts of crime superintended through navy information and non-navy information. Livestock constrated by shaper of law as a factors make heavier based on consideration about situation in particular Indonesia. In high criminal act robbing animal in particular at North Padang Lawas regency made an anxiety in society, level of robbing livestock because many factor which influense happened criminal act of robbing animal. There were factors happened robbing of livestock at Paluta (North Padang Lawas) content of economy factor, education factor, geographical and cultere factor. Some of cases robbing of livestock at North Padang Lawas got to comprehending if join with subject motivation for searched trofit to resist of verdict. Superintended robbing of livestock at Norh Padang Lawas through navy information adm non-navy information. The arrangement verdict culture based on Tumbaga Holing’s latter consist of verdict culture basics at North Padang Lawas regency in culture wide opened and flexible toward a new element in changed from outside or because alteration and development of area society. Curture of North Padang Lawas just written in Tumbaga Holling’sletter just could read by heart not witheyes so that the culture always everlasting. The alteration of culture not deleted a long culture and changed with a new, alteration happened because influence of events, influence of having to do with live inturns. Effectiveness from doubts applying agree with culture verdict grew up in North Padang Lawas society. Based on culture arrgements grew up and put on for generation until now could to applaying as criminal wisdom in efforts superintended criminal act of robbing livestock at North Padang Lawas regency. Keywords: Criminal wisdom, efforts of superintended, local of learning.